A mathematical model for hybrid-electric propulsion system for regional propeller-driven aircraft - Giuseppe Grazioso; Mario Di Stasio; Fabrizio Nicolosi; Salvatore Trepiccione (Energy Conversion and Management: X)
To address the environmental challenges in aviation, this research presents a novel mathematical model for simulating hybrid-electric powerplants in regional propeller-driven aircraft from the early design stages. The model integrates conventional thermal engines with battery and fuel cell systems, supporting up to two independent propulsion lines. Using a throttle-based approach, a linear mathematical formulation estimates power distribution within the architecture. A powerplant management algorithm enhances adaptability to varying power demands while ensuring a physically consistent solution. This approach enables rapid performance evaluation, allowing designers to optimize configurations from the earliest design stages. Case studies validate the model’s effectiveness in meeting diverse power requirements while maintaining a consistent solution. Ultimately, this study provides innovative analytical method for early-stage exploration and optimization of complex propulsion systems, contributing to a more sustainable aviation sector.